Ideological positioning through linguistic choices: critical stylistic analysis of Al Arabiya’s online news framing the 2017 Gulf crisis - Abdul Jabar, Mohd Azidan; Jasim, Samir A.; Jalaluddin, Ilyana; Abdul Halim, Hazlina (Transnational Press London, 2024)
The present study aims to conduct a critical stylistic analysis of Al Arabiya online news coverage of the 2017 Gulf crisis, focusing on the linguistic strategies sued by news reporters to convey ideological positioning. The study utilizes Jeffries’s critical stylistic framework (2010) and corpus methods to analyze a corpus compiled from Al Arabiya English covering the first month of the crisis. The research combines qualitative and quantitative methods to examine the ideological implications in the targeted media narrative, highlighting the use of naming and describing and equating and contrasting strategies. The analysis reveals that Al Arabiya has employed linguistic choices such as charged nouns, lexical ambiguity, complex noun phrases, and nominalization to reinforce Suadi Arabiya’s position, undermine Qatar’s credibility, and construct a negative narrative about Qatar. The study also identifies the use of equating and contrasting strategies to stigmatize Qatar, exaggerate threats, and support the anti-Qatar stance in the dispute. The findings demonstrate how Al Arabiya strategically uses language recourses and particular linguistics choices to shape readers’ perceptions and align them with the Saudi Arabiya’s geopolitical objectives in the Gulf crisis.